Analysis of spatial structure of latent effects governing hydrogeological phenomena - Lászlo Márkus; Olaf Berke; József Kovács; Wolfgang Urfer (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1998)
In the present study we investigate the data provided by the karstwater level monitoring system set up in the Transdanubian Mountains, more precisely in the Bakony, the Keszthelyi Mountains and the Balaton-Highland. (Here, like in the sequel, the term karstwater is used for groundwater in karstic areas.) The detailed description of the monitoring system itself and the geological and hydrogeological situation in which the system was planned to function and collect data about the water level can be found in Markus et al (1997) as well as the results of our previous study in determining the underlying (called also latent or background) effects driving the karstwater fluctuations.
Keywords: 519; Autoregressive Processes; Dynamic Factor Analysis; Geostatistics; Groundwater Hydrogeology; Infiltration; Spatially Referenced Time Series; Universal Kriging; Variogram